2017
DOI: 10.1016/j.psychres.2017.05.040
|View full text |Cite
|
Sign up to set email alerts
|

Stigma and discrimination experienced by people with schizophrenia living in the community in Guangzhou, China

Abstract: The aims of this study were to investigate experienced stigma and discrimination and their associated factors in people with schizophrenia who live in the community in Guangzhou, China. A total of 384 people with schizophrenia were randomly recruited from four districts of Guangzhou and completed the scales and questionnaires: Internalized Stigma of Mental Illness scale (ISMI), Self-Esteem Scale (SES), Discrimination and Stigma Scale (DISC-12), Brief Psychiatric Rating Scale (BPRS), PANSS negative scale (PANSS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
30
6
16

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(55 citation statements)
references
References 55 publications
3
30
6
16
Order By: Relevance
“…To our knowledge, this is the first study to examine the level of internalized stigma and related factors among people diagnosed with schizophrenia in Indonesia. We found that our sample was not demographically different from those of other similar studies in Taiwan, India, China and Singapore (Grover et al, 2017;Huang et al, 2018;Li et al, 2017;Picco et al, 2016) in terms of the gender, education levels and employment status distributions. Our subjects were more likely to be living with family than were those in other studies from similar collective societies in Taiwan and China (Huang et al, 2018;Li et al, 2017).…”
Section: Discussioncontrasting
confidence: 68%
See 1 more Smart Citation
“…To our knowledge, this is the first study to examine the level of internalized stigma and related factors among people diagnosed with schizophrenia in Indonesia. We found that our sample was not demographically different from those of other similar studies in Taiwan, India, China and Singapore (Grover et al, 2017;Huang et al, 2018;Li et al, 2017;Picco et al, 2016) in terms of the gender, education levels and employment status distributions. Our subjects were more likely to be living with family than were those in other studies from similar collective societies in Taiwan and China (Huang et al, 2018;Li et al, 2017).…”
Section: Discussioncontrasting
confidence: 68%
“…We found that our sample was not demographically different from those of other similar studies in Taiwan, India, China and Singapore (Grover et al, 2017;Huang et al, 2018;Li et al, 2017;Picco et al, 2016) in terms of the gender, education levels and employment status distributions. Our subjects were more likely to be living with family than were those in other studies from similar collective societies in Taiwan and China (Huang et al, 2018;Li et al, 2017). However, their psychotic symptoms were significantly less severe than those reported in other studies using the PSYRATS in south London and Indonesia (Craig et al, 2018;Erawati et al, 2014), possibly because our community sample was relatively more stable than those in other studies.…”
Section: Discussioncontrasting
confidence: 68%
“…It is thus of special note that the rate of IH is slightly increased annually, perhaps reflecting the use of this tool and suggesting that IH may have been under-utilized prior to the implementation of the law. In addition, China has far fewer psychiatric hospital beds per capita than other countries and thus patients who present for evaluation may be more likely to have an urgent need for hospitalization [12], and to be so severely impaired that their insight into their need for hospitalization is significantly compromised [10,13,14].…”
Section: Discussionmentioning
confidence: 99%
“…Previous research on hospitalized patients in China has shown that they differ from those in the US in having less insight into their condition. For example, in a sample of patients with schizophrenia (n = 384) living in the community in Guangzhou, 74% showed with partial or no insight into their illness, and insight was significantly and negatively correlated with medication compliance (r = − 0.356, p < 0.01) [14]. Mohamed [19].…”
Section: Discussionmentioning
confidence: 99%
“…[30] Çin'de yapılan çalışmada şizofreni hastalarının RHİDÖ puanının benlik saygısı ve deneyimlenen ayrımcılık puanı ile pozitif yönde önemli düzeyde ilişkili olduğu bulunmuştur. [34] Yapılan diğer bir çalışmada ise şizofreni hastalarının çoğunluğunun damgalanmaya karşı direncinin düşük olduğu ve kırsal kesimde yaşama, antipsikotik ilaca uyumda güçlük, yüksek düzey içselleştirilmiş damgalanma, yabancılaşma ve toplumsal yalıtımın damgalanma direnci ile istatistiksel olarak önemli düzeyde ilişkili olduğu bulunmuştur. [35] Yaşam kalitesi tedavi edici etkide bir ölçüt olup, şizofreni hastalarında uzun dönemde farmakolojik, ruhsal toplumsal tedavi, iyileştirim ve sağlık bakım maliyetleri gibi yaşamın tüm yönlerinde olumsuz etkilenmektedir.…”
Section: Discussionunclassified